APPROXIMATING A DSM‐5 DIAGNOSIS OF PTSD USING DSM‐IV CRITERIA. Issue 7 (4th April 2015) - Rosellini, Anthony J.; Stein, Murray B.; Colpe, Lisa J.; Heeringa, Steven G.; Petukhova, Maria V.; Sampson, Nancy A.; Schoenbaum, Michael; Ursano, Robert J.; Kessler, Ronald C.; On behalf of the Army STARRS Collaborators
<x xml:space="preserve">Abstract</x> Background Diagnostic criteria for DSM‐5 posttraumatic stress disorder (PTSD) are in many ways similar to DSM‐IV criteria, raising the possibility that it might be possible to closely approximate DSM‐5 diagnoses using DSM‐IV symptoms. If so, the resulting transformation rules could be used to pool research data based on the two criteria sets. Methods The pre–post deployment study (PPDS) of the Army Study to Assess Risk and Resilience in Servicemembers (Army STARRS) administered a blended 30‐day DSM‐IV and DSM‐5 PTSD symptom assessment based on the civilian PTSD Checklist for DSM‐IV (PCL‐C) and the PTSD Checklist for DSM‐5 (PCL‐5). This assessment was completed by 9, 193 soldiers from three US Army Brigade Combat Teams approximately 3 months after returning from Afghanistan. PCL‐C items were used to operationalize conservative and broad approximations of DSM‐5 PTSD diagnoses. The operating characteristics of these approximations were examined compared to diagnoses based on actual DSM‐5 criteria. Results The estimated 30‐day prevalence of DSM‐5 PTSD based on conservative (4.3%) and broad (4.7%) approximations of DSM‐5 criteria using DSM‐IV symptom assessments were similar to estimates based on actual DSM‐5 criteria (4.6%). Both approximations had excellent sensitivity (92.6–95.5%), specificity (99.6–99.9%), total classification accuracy (99.4–99.6%), and area under the receiver operating characteristic curve (0.96–0.98). Conclusions DSM‐IV symptoms can be used to approximate DSM‐5 diagnoses of PTSD among recently deployed soldiers, making it possible to recode symptom‐level data from earlier DSM‐IV studies to draw inferences about DSM‐5 PTSD. However, replication is needed in broader trauma‐exposed samples to evaluate the external validity of this finding.